2019
DOI: 10.2217/fon-2019-0310
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparity in Clinical Performance Between Multivariate Index Assay and CA125 in Detection of Ovarian Malignancy

Abstract: Aim: Based on evidence that African–American (AA) women have lower CA125 values than Caucasian (C) women, we investigated this to see if this disparity would have an impact on ovarian cancer detection using CA125 and multivariate index assay (MIA). Materials & methods: Serum from two prospective trials of 1029 (274 malignancies [250 C/24AA]) were analyzed for CA125 and MIA results. Clinical performance was calculated. Results: Sensitivity of MIA in Caucasian women was 93.2%, 74.4% for CA125 at the ACOG app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Evaluation of MIA across races demonstrated performance differences compared with CA125-II ( 47 ). A number of independent studies have shown that CA125-II levels are lower in non-Caucasian women ( 48 51 ).…”
Section: Evaluation Options Guidelines and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of MIA across races demonstrated performance differences compared with CA125-II ( 47 ). A number of independent studies have shown that CA125-II levels are lower in non-Caucasian women ( 48 51 ).…”
Section: Evaluation Options Guidelines and Implicationsmentioning
confidence: 99%
“…These two factors could cause CA 125-II to underperform in non-Caucasian populations. Sensitivity of MIA in Black women was 79% compared to a sensitivity of 62% with CA 125-II using the Dearking modified cutoffs of 67 U/mL for premenopausal women and 35 U/mL for postmenopausal women ( 47 , 53 ). Similar data was seen in comparison to ROMA in Black women, with the sensitivity of ROMA at 54% ( 54 ).…”
Section: Evaluation Options Guidelines and Implicationsmentioning
confidence: 99%
“…• Our highest score was for the previously mentioned 'Sequential afatinib and osimertinib in patients with EGFR mutation-positive non-small-cell lung cancer: updated analysis of the observational GioTag study' -Altmetric score: 96 [3]. • We also received high scores for Toni Leigh Mortimer (Stellenbosch University, South Africa) and colleagues' review 'Cannabinoids: the lows and the highs of chemotherapy-induced nausea and vomiting' and Charles Dunton (Vermillion, TX, USA) and colleagues' original research article 'Ethnic disparity in clinical performance between multivariate index assay and CA125 in detection of ovarian malignancy' [8,9]. Altmetric scores: 68 and 53, respectively.…”
Section: Content Highlights Of 2019mentioning
confidence: 99%
“…As an unusual glycoprotein, the expression of MUC16 is mainly located in the cell membrane or scattered in bodily fluids as a soluble form ( 9 ). MUC16 has been extensively used as a biomarker for ovarian cancer, and its expression has been associated with disease progression and has proven valuable in both detection and disease monitoring ( 10 , 11 ). It has also been reported that rising concentrations of soluble CA125 were detected in breast cancer, mesothelioma, gastric cancer, colorectal adenocarcinoma, etc.…”
Section: Introductionmentioning
confidence: 99%